THERMOACOUSTIC STUDIES IN ALKENYL LIQUID CRYSTALLINE COMPOUNDS - Nagesh, A.; Sailaja, D.; Reddy, K.Chandrasekhar (IJRDO-Journal of Applied Science, 2016)
Density of the liquid crystals can be measured by using a specially constructed sensitive dilatometer having two uniformly bored capillary arms of length around 30 cm above the bulb The volume of the dilatometer bulb and the volume of the capillary bore per cm were determined by calibrating it with triple distilled water, benzene and mercury and found to be 3.12916 cc and 0.00951 cc/cm respectively. The levels of the fluid in both capillary arms were recorded by using two traveling microscopes of least count 0.001 cm. The temperature variations of the volume of the dilatometer were recorded and corrections were made for it. All the weighing were done on sensitive K.Roy analytical single pan balance of sensitivity 0.00005 gm. The dilatometer was placed inside the INSREF solid state temperature bath and the temperature was controlled to an accuracy of  0.1C for making measurements at various temperatures.